Fracture geometry and statistics of Ceres' floor fractures. (August 2020) - Krohn, K.; von der Gathen, I.; Buczkowski, D.L.; Jaumann, R.; Wickhusen, K.; Schulzeck, F.; Stephan, K.; Wagner, R.; Scully, J.E.C.; Raymond, C.A.; Russell, C.T.
Abstract: Floor-fractured craters are one of the most distinct features on Ceres. Most of the fractures are located on the crater floors. The floor-fractures are concentric, radial or polygonal and share similarities with the floor-fractured craters (FCC) of Class 1 and 4 on the Moon (e.g., Buczkowski et al., 2018; Schultz, 1976) In total we measured 2336 fractures in thirteen craters. We analyzed their width, length, orientation and density. Floor-fractures on Ceres do not show a global uniform sense of orientation. Nevertheless, two or more preferred orientations can be found in nearly every crater. The density map illustrates that there is typically no decrease of fracturing from the crater center to the crater rim and denotes formation mechanisms that are not necessarily impact driven. Because of the variation in these parameters, it is more likely that FFC on Ceres are globally independent and show different formation mechanisms. The geometry of the floor-fractures suggests an inhomogeneous, brittle surface material, in some cases with volatile components. We also propose that the formation mechanisms on Ceres are comparable to those on the Moon and Mars and such mechanisms include cooling/melting processes, degassing, and subsidence of the crater floor by up-doming of subsurface material as a result of absolute tensile stresses. Highlights: We measured 2336 fractures in thirteen floor-fractured craters (FFC) on Ceres. Floor-fractured craters on Ceres share similarities with FFCs on other planetary bodies especially those on the Moon and Mars Some FFCs are impact-driven; other are related to cooling-melting processes, outgassing and/or tectonics such as doming. Fracture studies point out brittle surface materials.